Orbital socket contracture: a complication of inflammatory orbital disease in patients with Wegener's granulomatosis. Issue 4 (17th March 2005) - Talar-Williams, C; Sneller, M C; Langford, C A; Smith, J A; Cox, T A; Robinson, M R
Abstract : Aim: To describe the clinical characteristics of orbital socket contracture in patients with Wegener's granulomatosis (WG). Methods: A retrospective cohort study The medical records of 256 patients with WG examined at the National Institutes of Health from 1967 to 2004 were reviewed to identify patients with orbital socket contracture. Details of the orbital disease including Hertel exophthalmometry readings, radiological findings, and results of eye examinations were recorded. Orbital socket contracture was defined as orbital inflammation with proptosis followed by the development of enophthalmos and radiographic evidence of residual fibrotic changes in the orbit. To examine for risk factors in the development of a contracted orbit, patients with orbital socket contracture were compared to patients without contracture with respect to multiple variables including history of orbital surgery, orbital disease severity, and major organ system involvement. The main outcome measures were the clinical characteristics of orbital socket contracture associated with inflammatory orbital disease in patients with WG. Results: Inflammatory orbital disease occurred in 34 of 256 (13%) patients and detailed clinical data on 18 patients were available and examined. Orbital socket contracture occurred during the clinical course in six patients; the features included restrictive ophthalmopathy (five), chronic orbital pain (three), and ischaemic optic nerve disease (two) resulting in blindness (no light perception) in one patient. The orbital socket contracture occurred within 3 months of treatment with immunosuppressive medications for inflammatory orbital disease in five patients and was not responsive to immunosuppressive medications. The median degree of enophthalmos in the contracted orbit compared with the fellow eye was 2.8 mm (range 1.5–3.5 mm) by Hertel exophthalmometry. There were no risk factors that predicted development of orbital socket contracture. Conclusions: In six patients with WG and active inflammatory orbital disease, orbital socket contracture occurred during the treatment course with systemic immunosuppressive medications. The orbital socket contracture, presumably caused by orbital fibrosis, led to enophthalmos, restrictive ophthalmopathy, chronic orbital pain, and optic nerve disease and was not responsive to immunosuppressive therapy. Orbital socket contracture has not been previously reported as a complication of inflammatory orbital disease associated with WG and was an important cause of visual morbidity in our cohort of patients.